Implementing evidence into practice for the management of frozen shoulder: engaging with key stakeholders and evaluating barriers and facilitators using the Consolidated Framework for Implementation Research - Natalie Louise Clark; Melissa Johnson; Lucksy Kottam; Stephen Brealey; Joy Adamson; Amar Rangan; The UK FROST Stakeholder Group (Health Research Policy and Systems)
Abstract Background Frozen shoulder (FS) is a painful, stiff and disabling shoulder condition affecting adults of working age. A multi-centre randomised controlled trial (UK FROST) comparing three of the most common treatments provided by the National Health Service (NHS) in secondary care found all three treatments improved patient outcomes, with none being overall clinically superior. Each treatment had its advantages and disadvantages. This paper describes the use of the Consolidated Framework of Implementation Research (CFIR) as an exemplar of knowledge translation for the latest evidence from UK FROST in the management of FS. It describes using stakeholder feedback in the development of a FS pathway, considering the barriers and facilitators to implementation in relation to the UK FROST findings and current clinical practice. Methods Healthcare professionals, academics, policymakers and patient and public representatives were invited as stakeholders to three meetings held in November 2022 and January 2023. An overview of the United Kingdom Frozen Shoulder Trial (UK FROST) study, current pathways, referral processes and guidelines for FS in the context of the study results and the development of patient resources were discussed at the first meeting in November. Outcomes from this meeting informed the January meetings. The CFIR was used to guide analysis of the discussions from the stakeholder meetings. Results Overall, 67 stakeholders attended across three meetings. From the meetings, we categorised the FS pathway into four components (1) presentation and assessment; (2) initial management; (3) treatment options – physiotherapy and steroid injection, secondary care referrals; and (4) enhanced recovery and follow-up, with shared decision-making emphasised throughout the pathway. Barriers and facilitators in each of the pathway components were identified using the five domains of the CFIR. A proposed evidence-based FS pathway was developed with stakeholders using an eight-step process. Conclusions This study has led to the development of an evidence-based FS care pathway, ready to be considered by policymakers for implementation, with considerations of barriers and facilitators. There was consensus that it is feasible to embed a modified physiotherapy intervention form UK FROST within current primary and community care settings to optimise service delivery and referral pathways. Trial Registration The trial registration is ISRCTN48804508.